2017
DOI: 10.13189/ujcm.2017.050101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Comparative Values of Lipid Profile among Premenopausal and Postmenopausal Women

Abstract: Objectives: The study aims at comparing the changes of serum lipid levels in premenopausal women with that of postmenopausal counterparts. Study Design: An observational comparative and prospective study. Subjects and Method: One hundred healthy subjects (fifty each pre and postmenopausal women) between ages from 25 to 65 years, were selected for the study. They were nonsmoker, non-addict and not user of any hormonal contraceptive. The subjects were arranged in two age ranges of 25-45 years (group A) and 45-65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Lipid abnormalities are characteristically unique among post-menopausal women [11]. Although, raised total and LDL cholesterol has been observed with cardiovascular events but some of the studies revealed no association among them.…”
Section: Dyslipidaemiamentioning
confidence: 99%
“…Lipid abnormalities are characteristically unique among post-menopausal women [11]. Although, raised total and LDL cholesterol has been observed with cardiovascular events but some of the studies revealed no association among them.…”
Section: Dyslipidaemiamentioning
confidence: 99%